**Question:**

In the expansion \({\left( {2a – 1} \right)^6}\), the sum of the first three terms is:

**Reference explanation:**

**Correct Answer: EASY**

We have:

\(\begin{array}{l}

{\left( {2a – 1} \right)^6}\\

= C_6^0{.2^6}{a^6} – C_6^1{.2^5}{a^5} + C_6^2{.2^4}{a^4} – …

\end{array}\)

So the sum of the first 3 terms is \(64{a^6} – 192{a^5} + 240{a^4}\).

ADSENSE

=======================

MonToan.com shares with you the practice of multiple-choice tests according to the lesson of MATH 10. Multiple-choice questions with detailed answers help you compare and refer to assess your ability. I wish you all the best and success in your studies.